Pentingnya pendidikan bagi masa depan: Membentuk generasi unggul dan masyarakat berkualitas - Nisa’, Ismi Khoirun (Maliki Interdisciplinary Journal, 2024)
Education has an important role in forming a superior generation and quality society. Through education, one can acquire the knowledge, skills and undersanding needed to face the challenges of an ever-evolving world. Education can also help increase individual potential, create job opportunities, and promote innovation and social progress. Thus, it is important for us to recognize and encourage the importance of education to prepare for a brighter future so that we can change the paradigm of the younger generation to have broad insights.